Mitochondrial fragmentation, elevated mitochondrial superoxide and respiratory supercomplexes disassembly is connected with the tamoxifen-resistant phenotype of breast cancer cells - Tomková, Veronika; Sandoval-Acuña, Cristian; Torrealba, Natalia; Truksa, Jaroslav (Free radical biology & medicine, 2019)
Tamoxifen resistance remains a clinical obstacle in the treatment of hormone sensitive breast cancer. It has been reported that tamoxifen is able to target respiratory complex I within mitochondria. Therefore, we established two tamoxifen-resistant cell lines, MCF7 Tam5R and T47D Tam5R resistant to 5 μM tamoxifen and investigated whether tamoxifen-resistant cells exhibit mitochondrial changes which could help them survive the treatment. The function of mitochondria in this experimental model was evaluated in detail by studying i) the composition and activity of mitochondrial respiratory complexes; ii) respiration and glycolytic status; iii) mitochondrial distribution, dynamics and reactive oxygen species production. We show that Tam5R cells exhibit a significant decrease in mitochondrial respiration, low abundance of assembled mitochondrial respiratory supercomplexes, a more fragmented mitochondrial network connected with DRP1 Ser637 phosphorylation, higher glycolysis and sensitivity to 2-deoxyglucose. Tam5R cells also produce significantly higher levels of mitochondrial superoxide but at the same time increase their antioxidant defense (CAT, SOD2) through upregulation of SIRT3 and show phosphorylation of AMPK at Ser 485/491. Importantly, MCF7 ρ0 cells lacking functional mitochondria exhibit a markedly higher resistance to tamoxifen, supporting the role of mitochondria in tamoxifen resistance. We propose that reduced mitochondrial function and higher level of reactive oxygen species within mitochondria in concert with metabolic adaptations contribute to the phenotype of tamoxifen resistance.
Keywords: respirační komplex I; Mitochondria; fenotyp; tamoxifen; Phenotype; Superoxides; superoxidy; Reactive oxygen species; Cell Proliferation; reaktivní formy kyslíku; Xenograft Model Antitumor Assays; myši nahé; chemorezistence; nádory prsu; Breast cancer; Cell Movement; xenogenní modely - testy protinádorové aktivity; hormonální protinádorové látky; Reactive Oxygen Species; Animals; lidé; Tamoxifen; ženské pohlaví; Breast Neoplasms; Humans; zvířata; Tamoxifen resistance; pohyb buněk; Cell Cycle; nádorové buňky kultivované; myši; apoptóza; proliferace buněk; Electron Transport Complex I; Glycolysis; Tumor Cells, Cultured; Drug Resistance, Neoplasm; buněčný cyklus; Mice, Nude; Mice; Female; glykolýza; Antineoplastic Agents, Hormonal; Mitochondrial fragmentation; mitochondrie; Apoptosis